Evaluation of Public Sector Financial Management and Costing System in Improving Performance Effectiveness - Reynilda, Reynilda; Renal, Mohammad (STIE Amkop Makassar, 2025)
This study aims to evaluate the effectiveness of financial management strategies and costing systems in improving public sector performance. The research seeks to identify best practices that optimize resource allocation, enhance fiscal transparency, and strengthen accountability in public financial management by assessing the role of modern budgeting methods, costing techniques, and financial governance frameworks. This study employs a Systematic Literature Review (SLR) approach, synthesizing findings from recent empirical and theoretical research on financial management and costing systems in the public sector. It integrates analyses of performance-based budgeting (PBB), costing methodologies such as Activity-Based Costing (ABC) and Zero-Based Budgeting (ZBB), and digital innovations in fiscal governance. The findings indicate that adopting performance-driven budgeting and precise costing methodologies improves budget efficiency by ensuring expenditures are linked to measurable outcomes. The study highlights that transparency and accountability mechanisms, including independent audits and open financial reporting, mitigate corruption risks and enhance public trust in financial governance. However, challenges such as institutional resistance, political interference, and technological limitations hinder the successful implementation of these financial management frameworks. This study provides critical insights for policymakers and financial managers in strengthening public financial governance. The findings suggest that integrating digital innovations, enforcing stricter regulatory oversight, and fostering greater citizen engagement in budgetary processes can significantly improve fiscal sustainability. Future research should explore the long-term impact of these financial strategies, particularly in low- and middle-income economies, where financial governance remains a critical challenge.